Effect of H-NS protein on the virulence of Burkholderia thailandensis - WEI Leilei; MO Fei; WANG Chunyan (陆军军医大学学报)
Objective To construct hns gene overexpression strains of Burkholderia thailandensis BPM, and explore the effects of hns overexpression on bacterial growth, motility, biofilm formation ability and susceptibility to antimicrobial drugs. Methods The hns genes 03253 and 05307 were respectively cloned into the expression vector pTAC-Cm to yield recombinant vectors pTAC-03253 and pTAC-05307. Then the 2 types of plasmids were electroporated into the BPM competent strain to obtain recombinant strains, and their phenotypic changes in growth, motility, biofilm, and drug sensitivity were detected. Results The strains of hns overexpression were successful constructed, and they presented significantly inhibited growth and motility, markedly enhanced ability to form biofilms, decreased sensitivity to levofloxacin and minocycline when compared with the wild-type BPM strain. Conclusion H-NS protein plays an important role in the regulation of virulence and drug resistance in Burkholderia thailandensis BPM, and can become a new target for the treatment of infections caused by Burkholderia thailandensis.